Manifestasi Kehadiran Allah dalam Bait-Nya: Proklamasi Firman, Bahasa Roh, dan Nubuat dalam 1 Korintus 14 - Suwanto, Wilson W. (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2024)
This article examines 1 Corinthians 14 to address the research question: How is God's presence manifested in the church as His temple? The objective is to analyze Paul's teaching to determine how practices in the Corinthian church's worship align with its identity as God's temple. The method is textual analysis of the passage, informed by scholarship on the Corinthians' context. Paul asserts that the Corinthian church fails to live out its identity as God's temple when members speak in uninterpreted tongues during worship. These tongues do not clearly proclaim God's word and hinder unbelievers from encountering God’s presence. In contrast, prophecy entails proclaiming the gospel understandably through the Spirit to build up believers' faith and provide unbelievers an opportunity to worship God. Thus, the practice of prophecy better aligns with the missional identity of the church as God's temple compared to uninterpreted tongues. The article concludes that churches today should prioritize clear preaching over ecstatic speech in worship services to manifest God's presence. This contributes a framework for assessing worship practices based on how they proclaim the word to make God's presence tangible to believers and unbelievers alike.